(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Background: Neurosurgery is a traditionally male-dominated field due to various factors such as limited mentorship, lack of role models, and challenges related to childbearing and childcare, which have reduced women’s representation. This study aims to analyze career trajectories of female neurosurgeons in Bangladesh, highlighting their achievements, the obstacles they overcame, and the strategies that enabled them to thrive. Their paths will promote women’s empowerment and leadership in neurosurgery thus inspire future generations. Materials and method: This descriptive study analyzed and documented the professional journeys of seven female neurosurgeons who practiced in Bangladesh between 2006 and 2025. Data were compiled from professional biographies, institutional records, and neurosurgical society archives. The study examined key milestones including academic progression, overseas training, leadership roles, participation in international forums, and contributions to neurosurgical education. The analysis focused on identifying the challenges and enabling factors that contributed to their growth as mentors and role models in the field. Result: As of 2025, Bangladesh has 259 neurosurgeons, of whom only 7 (2.7%) are women. Among them, one serves as a full professor and head of a neurosurgery department. Six (85.7%) have completed overseas fellowships in various neurosurgical subspecialties, and all seven (100%) have participated in international conferences and hands-on surgical workshops abroad. Three (42.9%) currently serve on executive committees of international neurosurgical societies. The number of female neurosurgery residents has shown steady growth, reaching 37 out of 265 (13.96%) in 2025—reflecting increasing interest and access over the past five years. Conclusion: Despite systemic and societal barriers, these female neurosurgeons in Bangladesh have demonstrated resilience, excellence, and leadership. By breaking longstanding gender barriers, they have become role models for the next generation, both in Bangladesh and globally. Bang. J Neurosurgery 2025; 14(2): 100-106